Pelatihan Personal Branding dan Pembuatan Video Content sebagai Sarana Video Promosi Kreatif pada Masyarakat Desa Jlegong Pagerkukuh Kabupaten Wonosobo - Dwi Korina Relawati; Sudono Sudono; Siti Sarifah; Shinto Dwirawati; Basirun Basirun; Diyah Ayu Karunianingsih; Kusumo Gambrianto; Siti Asiatun; Mufadhol Mufadhol (Lembaga Pengembangan Kinerja Dosen, 2025)
Social media has a significant position as a means of promotional media in building branding. Optimization of social media needs to be done with quality and consistent content as a promotional media through promotional videos. Creative promotional video production training is an effort to improve digital competence for the community, community, institutions and stakeholders. Training on making content videos and personal branding at SMPIT Desa Jlegong, Pagerkukuh, Wonosobo, was carried out using participatory methods and direct practice to improve participants' skills optimally. This activity was attended by 40 participants who were divided into 4 small groups so that the learning process was more effective and interactive. Each group was facilitated by three mentors. The project challenge was given to create video content that was relevant to their personal or institutional identity, then presented as an evaluation of learning outcomes. The results of this training, the content produced reflects the participants' ability to apply theory to practice, including the use of narratives, visuals, and simple editing. The conclusion of this activity, content videos and personal branding at SMPIT Desa Jlegong were successfully implemented and had a positive impact on increasing digital literacy, creativity, and self-awareness of participants.